Understanding whole person systems in brain-gut-microbiome research through ultra-high-field MRI imaging - Tien S. Dong; Kay Jann; Danny J.J. Wang; Arpana Church (NeuroImage, 2025)
The brain-gut-microbiome (BGM) axis regulates interoception, metabolism, and immunity, with dysfunction linked to IBS, obesity, and mood disorders. Ultra-high-field (UHF) MRI advances neural imaging, enhancing resolution of vagal and spinal circuits mediating gut-brain communication. UHF enables real-time tracking of interventions like vagus nerve stimulation and probiotics, linking microbiome shifts to neural adaptations. Despite challenges like signal distortions, innovations in coil design are improving imaging fidelity. Integrating neuroimaging with multi-omic profiling fosters a systems-level approach, advancing personalized therapies for BGM disorders. This commentary underscores UHF MRI’s transformative potential in bridging neuroscience, microbiome science, and clinical applications.